The stability of oligodeoxyribonucleotide duplexes containing degenerate bases. - Anand, N N (Nucleic Acids Res, 1987)
Oligodeoxyribonucleotides containing N4-methoxycytosine (mo4C), N4-methoxy-5-methylcytosine (mo4m5C) and other base-analogues were synthesised and used to compare the stabilities of duplexes containing mo4C.A and mo4C.G base pairs with those containing normal and mismatch pairs. The Tm values and other thermodynamic parameters are recorded. The otherwise identical duplexes containing a mo4C.A and a mo4C.G base pair have closely similar stabilities to each other and to the corresponding duplexes containing normal base pairs, considerably greater than the stabilities of those containing mismatch pairs. Corresponding observations are recorded in dot-blot experiments using M13 cloned DNA carrying an insert complementary to the oligonucleotides; approximate Td values are given. IMAGES: